Flight Route Optimization in Required Navigation Performance (RNP) Approach Flight Procedures Based on Experimental Algorithm - Sonhaji, Imam; Fatonah, Fety; Jatmoko, Djoko (Proceeding of International Conference of Advanced Transportation, Engineering, and Applied Social Science, 2023)
ICAO recommends that capacity and efficiency achievement programs be carried out through the Performance Based Navigation (PBN) implementation model. This research aims to obtain an overview of the optimal formula model that can be implemented into flight paths based on the RNP approach procedure for flight path efficiency and fuel efficiency. This research uses quantitative experimental methods. The results of this research are that the optimization model at minimum speed (V=210 knots) produces route effectiveness of 8% and fuel savings of 1.5% compared to the established current procedure. The conclusion is that for straight paths, route optimization is achieved by applying the maximum speed, but for circular (arc) paths, route optimization is achieved by applying the specified minimum speed.